2014
DOI: 10.1088/0031-9155/59/19/5873
|View full text |Cite
|
Sign up to set email alerts
|

Over-response of synthetic microDiamond detectors in small radiation fields

Abstract: The recently commercialized PTW microDiamond detector (T60019) has been designed for use in small radiation fields. Here we report on the measurement of relative output ratios for small fields using five microDiamond detectors. All of the microDiamond detectors over-responded in fields smaller than 20 mm, by up to 9.3% for a 4 mm field. The over-response was independent of accelerator type and choice of collimation. The over-response was slightly larger than that observed in silicon diodes. Since all five micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
73
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 14 publications
13
73
4
Order By: Relevance
“…The correction factors resulted ≈2% lower than those proposed by Ralston et al 31 16 on a CyberKnife system. Our dose response ratios thus result in an acceptable agreement with the already published ones, bearing in mind the different conditions in which those results were obtained.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The correction factors resulted ≈2% lower than those proposed by Ralston et al 31 16 on a CyberKnife system. Our dose response ratios thus result in an acceptable agreement with the already published ones, bearing in mind the different conditions in which those results were obtained.…”
Section: Discussioncontrasting
confidence: 64%
“…As reported in two recent papers, indeed, the physical density of the detector is the dominant parameter in small fields. 30,31 In large fields, instead, the mass energy absorption coefficient dominates. If no volume averaging were present, there would be an over-response of finite size detectors in such small fields.…”
Section: Discussionmentioning
confidence: 99%
“…Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 . Monte Carlo simulations have shown that the magnitude of overresponse is proportional to the mass density of the material in the volume of interest, with a larger overresponse determined for a voxel of the same size in a radiation beam for diamond than for silicon in a 5 mm field for 15 MV (38) .…”
Section: Discussionmentioning
confidence: 99%
“…If the dose distribution across the circular integration area has a circular symmetry, then an alternative integration method using high‐resolution scanned dose profiles can be employed 15, 25, 26. Table 1 lists the type of detectors used for each instance where we used this method, a general description of which is given here.…”
Section: Methodsmentioning
confidence: 99%